Perbandingan Data Hasil Metode B&W dan GWC untuk Klasifikasi Slagging Abu Batu Bara LRC - Denny Murdany Muchsin (Sekolah Tinggi Teknik - PLN, 2021)
Slagging classification is generally listed in coal COA in coal trading transactions using one of the methods of determining slagging classification so that coal is ensured boiler friendly (low/medium classification). The paper aims to prove the tendency of two methods of determining slagging classification (B&W and GWC) on the results of certain classifications in LRC coal. The research method uses a quantitative method by collecting LRC coal COA data on a coal-fired steam power plant for a year of coal receipt (81 lots) issued by a laboratory that has been accredited by KAN (National Accreditation Committee). According to the method of GWC, ashes of entire lots are classified as LRC ash. While the method of B&W, there are 62 lots of ash classified as lignitic ash and 19 lots of ash classified as bituminous ash. This research has shown that the GWC method shows 79 lots of ash (97.53%) has low and medium classification and 2 lots of ash (2.47%) have a high classification; the method from B&W shows 19 lots of ash (23.46%) has a low classification and 62 lots of ash (76.54%) has a severe classification.